2009
DOI: 10.1017/s0376892909005347
|View full text |Cite
|
Sign up to set email alerts
|

The status of anthropogenic threat at the people-park interface of Bwindi Impenetrable National Park, Uganda

Abstract: Effective management of anthropogenic threats is key to sustaining biological diversity in protected areas. Types and distribution of threats to Bwindi Impenetrable National Park, Uganda were investigated to assess the Park's status 12 years after it was upgraded from a forest reserve to a national park. Bwindi, like many tropical forested parks, is surrounded by dense human populations. Threats were quantified in 104 1-km edge-interior transects set around the Park. The distribution of threats was patchy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 37 publications
0
44
1
1
Order By: Relevance
“…Although human disturbance studies inside forested national parks are rare (Robbinset al 2006), in East Africa, extraction of woody biomass is consistently identified as the most widespread disturbance (Bleher et al 2006;Baranga 2007;Olupot et al 2009). The most pervasive need for wood is for fuel (Dovie et al 2004;Naughton-Treves et al 2007), followed by poles for construction and hardwoods to make charcoal (Baranga 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although human disturbance studies inside forested national parks are rare (Robbinset al 2006), in East Africa, extraction of woody biomass is consistently identified as the most widespread disturbance (Bleher et al 2006;Baranga 2007;Olupot et al 2009). The most pervasive need for wood is for fuel (Dovie et al 2004;Naughton-Treves et al 2007), followed by poles for construction and hardwoods to make charcoal (Baranga 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies to measure human disturbance in tropical protected forests in India, Kenya and Uganda (Barve et al 2005;Bleher et al 2006;Baranga 2007;Olupot et al 2009), recommended measuring trees cut for any purpose (all sites), signs of poaching (two sites), evidence of burning (two sites), in-park cultivation (three sites), pits to saw timber (one site), livestock grazing (four sites), charcoal-making (two sites) and extraction of a wide range of non-timber forest products (three sites).…”
Section: Field Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that while the MUP idea was innovative two decades ago, park management in Bwindi remains conservative with regards to NTFPs harvest. Despite these restrictions, local people continue to illegally harvest the resources disregarding the risks of arrests, imprisonments, and fines (Namara 2006;Olupot et al 2009;Shova & Hubacek 2011;Twinamatsiko et al 2014). The unauthorized NTFPs may contribute a significant amount of income to households in Bwindi , which may be the reason local people risk their harvests.…”
Section: Important and Preferred Ntfps For The Local Peoplementioning
confidence: 99%
“…Wildlife species found in unprotected forests face the direct pressure of human disturbance as well as indirect pressures resulting from human modification of their habitats (Olupot et al 2009). The 3 village communities living at MH (43 km 2 ) have a combined human population of ~400 inhabitants.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%